PROTECTION ACTIVITY OF T CELL LYMPHOKINES AGAINST INFECTIOUS BURSAL DISEASE IN LAYER PULLETS - Mushtaq T. B. Al-Zuhariy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The present study was aimed to administering hyperimmunized avian salmonella-immune lymphokines (S-ILK) to 200 one-day-old layer pullets to improve the immunological response against Gumboro (IBDV) divided into four groups. On the first day, the following was applied to all groups: G1: intraperitoneal injection of 0.50 mL S-ILK followed by a 30-minute challenge with 0.1 mL IBDV (ELD50 103.2); G2: intraperitoneal injection of 0.5 mL of S-NILK followed by a 30-minute challenge by 0.1 mL IBDV. G3: challenged with 0.1 mL of IBDV only, G4: uninfected, unchallenged group consider as a negative control. The results of the findings indicated the greatest a statistically significant rise (p≤ 0.05) in IgG and IFN-γ titres in that group and the viral load test revealed that at 7 and 14 days after infection, The largest number of IBDV RNA copies were found in G2 and G3. in the bursa of Fabricius. The first group had the lowest mortality rate compared to the other groups. Early S-ILK administration improves maternal resistance to IBDV infection and inhibits viral replication in the fabricius bursa following IBDV challenge. Thus, we may reduce the amount of time, effort, and money spent on immunization procedures that do not completely protect against diseases.